(untitled) (Società e diritti, 2025)
The term "violence" is conceptually (also from an etymological point of view) contiguous to the concept of violation of a regulatory precept. When a harmful or potentially harmful action is considered legally permissible, it is not defined, except in a non-technical way, as "legitimate violence". There are other syntagms adopted: legitimate use of force, legitimate defense, etc. Violence is never legitimate and “produces” victims who, in addition to suffering the material effects of violence, whether more or less physical, more or less long-lasting or more or less curable, suffer the collateral effects connected to the development of the procedural dynamics. The condition of victim is certainly among those social obstacles that prevent the full development of the human person ( or being?) and which the Constitution also requires the Republic to remove. The protection given to the legal system by art. 3 and other relevant constitutional articles were considered for years to be more than sufficient for the protection of victims, so much that no legislative initiatives for modification or additions were initiated until 2005. Since that year there has been a succession of legislative initiatives aimed at giving an autonomous and declined constitutional relevance to the victim. The analysis of the laws, of the parliamentary dynamics and of the size of the proposed modifications, shows how the growing need for protection felt by the population has, depending on the case, generated political oppositions. The same laws, as a matter of fact, have often been stopped in the bud, or on the contrary, have given rise to mere "manifesto initiatives" that have not gone beyond the presentation.